Perceived ageism and psychosocial outcomes during the COVID-19 pandemic - André Hajek; Hans-Helmut König (BMC, 2024)
Abstract Background In light of the existing knowledge gap in this research area (particularly based on representative samples and research conducted during the pandemic), the objective of this study was to explore the association between perceived ageism and psychosocial outcomes (i.e., in terms of life satisfaction, loneliness, social isolation, aging satisfaction and depressive symptoms) among middle-aged and older adults during the COVID-19 pandemic based on nationally representative data. Methods We used data from the nationally representative German Ageing Survey, which covers community-dwelling middle-aged and older individuals aged 40 years or over. Specifically, wave 7 of the German Ageing Survey (conducted from November 2020 to March 2021) was analyzed, consisting of a sample of 4,167 individuals with an average age of 68.7 years (SD: 10.1 years; ranging from 46 to 98 years). Established instruments were employed to measure psychosocial outcomes. Results Regressions showed that the presence of perceived ageism was significantly associated with unfavorable psychometric outcomes (i.e., higher loneliness: β = 0.29, p < 0.001; higher perceived social isolation: β = 0.32, p < 0.001; more depressive symptoms: β = 2.68, p < 0.001; lower life satisfaction: β=-0.28, p < 0.001; higher negative affect: β = 0.21, p < 0.001; lower aging satisfaction: β=-0.19, p < 0.001), except for positive affect (β=-0.06, p = 0.10). Stratified by age group (i.e., individuals 40 to 64 years; individuals aged 65 years and over, see Tables 3 and 4), comparable results were obtained in terms of significance. Conclusions Perceived ageism was associated with unfavorable psychosocial outcomes. This knowledge can help reduce vulnerability to negative psychosocial factors in people in the middle and later years of life.